# Cos 2x = check all that apply.

Its a, and c and I'm not sure so sorry if I'm wrong

x + x + 6 - 7 + x

3 - x + 2x - 4 + 2x

Step-by-step explanation:

I just did the assignment.

Hope this helped ;w;

Step-by-step explanation:

After you enter the expression, Algebra Calculator will print a step-by-step. Here are some examples: y=2x^2+1, y=3x-1, x=5, x=y^2. For example the command 2x at 3 evaluates the expression 2x for x=3, which is equal to 2*3 or 6. If we instead try a value that doesn't work, say x=3 (try 2x+3=7 at 3)

idk

step-by-step explanation:

use that smart brain

a and c

Step-by-step explanation:

3x-1

Step-by-step explanation:

1 and 3

Step-by-step explanation:

The equation can be arranged to form equations 1 and 3.

Hope this helps

3x-7+ 6

Step-by-step explanation:

Group the x factors together and write them iut in groued pairs witht the same type terms and dd them up to get 3x and just put in the 6 and -7.

3x-1
Hope this helps...

see below

Step-by-step explanation:

The double angle formulas for trig functions are generally based on the sum of angle formulas, where the two angles are equal.

cos(a+b) = cos(a)cos(b) -sin(a)sin(b)

When a=b=x, then ...

cos(2x) = cos(x)² -sin(x)²

The Pythagorean identity can be used to substitute for either of the squares:

cos(2x) = (1 -sin(x)²) -sin(x)²

cos(2x) = 1 - 2sin(x)²

or

cos(2x) = cos(x)² -(1 -cos(x)²)

cos(2x) = 2cos(x)² - 1

### Other questions on the subject: Mathematics

Hello! the answer is: the correct option: b. [tex]x=2.23[/tex]why? to solve the problem, we need to remember how to operate to simplify exponential expressions using the logarithms...Read More
Mathematics, 21.06.2019, ciya12
what is the graphstep-by-step explanation:...Read More